Beginnings of Indian Astronomy with Reference to a Parallel Development in China - Parpola, Asko (History of Science in South Asia)

(untitled) (University of Alberta Library, 2013)
Hypotheses of a Mesopotamian origin for the Vedic and Chinese star calendars are unfounded. The Yangshao culture burials discovered at Puyang in 1987 suggest that the beginnings of Chinese astronomy go back to the late fourth millennium BCE. The instructive similarities between the Chinese and Indian luni-solar calendrical astronomy and cosmology therefore with great likelihood result from convergent parallel development and not from diffusion.